2021
DOI: 10.1177/1087054720978556
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sleep and Circadian Rhythms in Children with Attention Deficit Hyperactivity Disorder

Abstract: Objective: Children and adults with ADHD often report sleep disturbances that may form part of the etiology and/or symptomatology of ADHD. We review the evidence for sleep changes in children with ADHD. Methods: Systematic review with narrative synthesis assessing sleep and circadian function in children aged 5 to 13 years old with a diagnosis of ADHD. Results: 148 studies were included for review, incorporating data from 42,353 children. We found that sleep disturbances in ADHD are common and that they may wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 209 publications
(349 reference statements)
2
42
0
Order By: Relevance
“…Only the extent of sleep deficit was slightly higher in children with ADHD on school days than on free days as compared with controls. These findings are in line with the results of a recent meta-analysis [4], which revealed longer SOL and lower sleep efficiency, and with a systematic review on schoolaged children with ADHD [27], which confirmed the occurrence of sleep disturbances using subjective and objective measurement methods in ADHD. With regard to IIV, children with ADHD showed higher IIV than typically developing children only in the SOL, which confirms the results of some earlier studies [39,70], but also contradicts others [40,41] that did not find greater IIV in children with ADHD.…”
Section: Discussionsupporting
confidence: 90%
“…Only the extent of sleep deficit was slightly higher in children with ADHD on school days than on free days as compared with controls. These findings are in line with the results of a recent meta-analysis [4], which revealed longer SOL and lower sleep efficiency, and with a systematic review on schoolaged children with ADHD [27], which confirmed the occurrence of sleep disturbances using subjective and objective measurement methods in ADHD. With regard to IIV, children with ADHD showed higher IIV than typically developing children only in the SOL, which confirms the results of some earlier studies [39,70], but also contradicts others [40,41] that did not find greater IIV in children with ADHD.…”
Section: Discussionsupporting
confidence: 90%
“…The effect on sleep onset latency is of significant importance, given that problems with prolonged sleep onset latency are more common in children with ADHD than among healthy peers [ 32 , 33 ]. About one-third of children with ADHD have difficulties falling asleep [ 3 , 44 ], with up to one hour of sleep onset latency between children with ADHD and healthy peers [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD have an increased risk of poor health outcomes, compared to healthy peers. The negative behaviors associated with ADHD cause difficulties with interpersonal interactions and educational outcomes, and are likely to be exacerbated by sleep disturbances [ 3 ]. The prevalence of sleep disturbances among children with ADHD is high (up to 70%) [ 4 , 5 ], compared to healthy peers (20–30%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations